A novel cup with a pressure-adjusting mechanism for high-temperature water vapor transmission rate measurements. (April 2016) - Iizuka, Shinya; Murata, Kazuhide; Sekine, Masahiro; Sato, Chiaki
Abstract: Water vapor transmission rate (WVTR) measurements with the conventional cup method do not yield accurate values at high temperatures because the film specimens deform and are damaged owing to air expansion in the cup. A new cup with a pressure-adjusting mechanism allows measurements at 85 °C and prevents specimen deformation and damage. WVTRs of polypropylene (PP) and polyethylene terephthalate (PET) measured with the new cup method are the same as those measured with the conventional cup method at 40 °C, and gas chromatographic detection method at 60 °C and 85 °C. Arrhenius plots of the water vapor permeability coefficient of PP, polyethylene naphthalate (PEN) and polyimide (PI) with the new cup method show a linear relationship in the range 25–85 °C. In the same range, Arrhenius plots of PET, polybutylene terephthalate (PBT) and polylactic acid (PLA) have bending points corresponding to the glass transition temperatures of the materials.